Inducible Bronchus-Associated Lymphoid Tissue: Taming Inflammation in the Lung - Hwang, Ji Young; Randall, Troy D.; Silva-Sanchez, Aaron (Frontiers in Immunology, 2016)
Following pulmonary inflammation, leukocytes that infiltrate the lung often assemble into structures known as inducible Bronchus-Associated Lymphoid Tissue (iBALT). Like conventional lymphoid organs, areas of iBALT have segregated B and T cell areas, specialized stromal cells, high endothelial venules and lymphatic vessels. After inflammation is resolved, iBALT is maintained for months, independently of inflammation. Once iBALT is formed, it participates in immune responses to pulmonary antigens, including those that are unrelated to the iBALT-initiating antigen, and often alters the clinical course of disease. However, the mechanisms that govern immune responses in iBALT and determine how iBALT impacts local and systemic immunity are poorly understood. Here we review our current understanding of iBALT formation and discuss how iBALT participates in pulmonary immunity.